Accessibility and Its Impact on Third-Party Funds in Indonesian Islamic Banking - Ahyar, Muhammad Khozin; Hakim, Abdul (Journal of Finance and Islamic Banking, 2023)
This study aims to analyze the impact of financial inclusion variables on third-party funds (DPK) in Islamic banking. The variables analyzed include both financial inclusion and non-financial inclusion factors. Financial inclusion variables are represented by office networks, ATM networks, and the number of savings customers. Meanwhile, non-financial inclusion variables include DPK, interest rates, profitability, yield equivalent, and the size of Islamic banking institutions. This research uses a quantitative approach with the Vector Error Correction Model (VECM) and Eviews as the analysis tool. The findings reveal that the financial inclusion variables significantly influencing Islamic banking deposits are the office network (KTR), ATM network (ATM), and the index of the number of DPK accounts per 1000 adult population (IRDPK). These results indicate that expanding banking infrastructure and increasing access to financial services play a critical role in boosting Islamic banking deposits. This study contributes to understanding how financial inclusion factors interact with other banking variables to shape the performance of Islamic banks in Indonesia, providing insights for policymakers and financial institutions in enhancing financial accessibility and deposit mobilization.